Consistent Evidence on Duration Dependence of Price Changes - Alvarez, Fernando; Borovičková, Katarína; Shimer, Robert (American Economic Review, 2025)
We develop a linear GMM estimator of the discrete-time mixed proportional hazard (MPH) model of duration with an arbitrary distribution of unobserved heterogeneity. We allow for competing risks, observable characteristics, and censoring. We prove our estimator is consistent and apply it to the duration of price spells. We find substantial unobserved heterogeneity with economically meaningful implications for the response of output to a monetary policy shock in a model with time-dependent pricing rules and for the degree of state dependence in a model of price plans. (JEL C24, C41, E23, E31, E52, L11)